Lila & Other Stories - Kona, Bongani (School of Languages and Literatures, 2022)
A survivor of the Chimoio bombings, conducted by the Rhodesian Security Forces against the Zimbabwe African National Liberation Army (ZANLA) headquarters in Mozambique, attempts to send a dog to the moon. After seven years of failing to conceive a couple gives birth to a baby plagued by an infinite hunger. A teenage girl recalls the day her father took her to the execution of The Colonel: the arm-wrestling champion of the 153rd State ... The departure point for most of the stories in this collection is my own upbringing in Harare, Zimbabwe, in the 1990s and early 2000s. Given the country's repressive political history, I've been asking myself the question: in what new ways can we write about oppressive states? What new metaphors, vocabularies can we come up and how can we capture, in writing, the many forms of violence they deploy against their citizens? And more crucially, how do we depict the way ordinary citizens find ways, sometimes bizarre, of resisting this onslaught of violence from the state? Lila & Other Stories is a small attempt to create something meaningful out of a history I and many others are still grappling with.